Solidarity: The Unfulfilled Project of Polish Democracy - Krzemiński, Ireneusz (Studies in Political Transition, 2019)
This book is a collection of essays which span three decades, capping research into the Polish Solidarity movement and its impact on social change. The major one reports on the author's 1981 study on the formation of the Solidarity movement and trade union, one of two research projects on Solidarity carried out at the time. The idea of debating (deliberative) democracy fostered by Solidarity proved an unfulfilled utopia. It was abandoned by the new political elite and by Poles, who used freedom to develop individual, ambitious and aggressive career paths in order to attain West-European living standards. While Polish religiosity and the Catholic Church, led by Pope John Paul II, vitally promoted peaceable resistance to communism, now the Church has morphed into an anti-democratic political and cultural actor.